Optimization of Fuel Cost in Electric Power Systems using Harmony Search Algorithm - Yıldırım, Ayşe Erdoğan (Kırıkkale Üniversitesi, 2021)
Fuel Cost Optimization emerges as an important issue in electrical load distribution systems. In this study, the performance of Harmony Search Algorithm, which has a significant place in the literature, has been observed for a sample problem in the field of fuel cost optimization. It is aimed to distribute the load provided by a three-unit power plant with minimum cost. Three restricted functions are defined in order to calculate the energy production cost per hour of three thermal power plants. For this reason, the problem has been solved by using equal weighted scalarization, one of the multi-objective optimization techniques and static penalty function with Harmony Search Algorithm. The obtained results are presented in comparison with the Lagrange solution and Artificial Bee Colony Algorithm, which were used to solve the same problem.
Keywords: Engineering; Mühendislik; Electrical Engineering; Elektrik Mühendisliği